The Influence Of Experience, Satisfaction And Service Quality On Word Of Mouth Intentions And Customer Loyalty - Sutriani, Sutriani; Muslim, Muslim; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Customer satisfaction is very important for business because high customer satisfaction will increase company profits. The aim of this research is to examine service quality, where positive service quality has major implications for customer assessment, has an impact on customer satisfaction and customer satisfaction itself has an influence on customer loyalty and word of mouth intentions. This research used a purposive sampling method involving 150 non-local fashion brand customers from Tangerang and Jakarta. Data analysis uses Structural Equation Modeling (SEM). This research produces findings including that customer experience has a negative effect on customer loyalty, service quality has a positive effect on customer satisfaction which ultimately has a positive effect on customer loyalty and word of mouth intentions. There are several limitations to this research, including only using one industry as the research object, an online questionnaire distribution system and the need to add other variables to expand the findings so that it is hoped that future researchers can fill these gaps. Keywords: Customer Satisfaction, Customer Experience, Service Quality, Customer loyalty, Word Of Mouth (WOM)